1945
DOI: 10.1111/j.1365-2621.1945.tb16173.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Characteristics, Tenderness, and Drip Losses of Beef in Relation to Temperature of Freezing

Abstract: As a result of earlier studies by two of the present authors and other workers, the fact seemed well established that the temperature of freezing has an important bearing on tenderness and on the drip loss of meat in thawing. To determine the basic cause of these effects was an obvious need. The purpose of the studies reported here was to throw light on the relation between the histological characteristics of beef frozen at different temperatures, on one hand, and tenderness and drip loss of the product, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1955
1955
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…The intracellular ice crystal formation arising from fast freezing has been shown to result in fiber splitting and damage which in some cases (Hiner et al, 1945;Hiner and Hankins, 1947;Carroll et al, 1981) has been associated with greater tenderness.…”
Section: Resultsmentioning
confidence: 96%
“…The intracellular ice crystal formation arising from fast freezing has been shown to result in fiber splitting and damage which in some cases (Hiner et al, 1945;Hiner and Hankins, 1947;Carroll et al, 1981) has been associated with greater tenderness.…”
Section: Resultsmentioning
confidence: 96%
“…The impact of freezing rates on meat tenderness has been debated by several researchers. The positive fast freezing impact on meat tenderness has been reported, where quick frozen samples showed less resistance to shearing or higher scores of sensory tenderness compared to slow frozen counterparts (Hiner, Madsen, & Hankins, 1945;Petrović et al, 1993). In contrast, no substantial freezing rate effect on eating quality attributes of beef including tenderness and water-holding capacity has also been reported (Hergenreder et al, 2013;Paul & Child, 1937).…”
Section: Shear Force and Desmin Degradationmentioning
confidence: 88%
“…3). Numerous studies have found a tenderising effect of freezing/thawing (Hankins & Hiner, 1938;Hiner et al, 1945;Leygonie et al, 2012a;Petrović et al, 1993;Shanks, Wulf, & Maddock, 2002;Vieira et al, 2009), which is likely associated with the loss of structural integrity induced by ice crystal formation (Leygonie et al, 2012a). Furthermore, ageing-then-freezing might allow the formation of intracellular crystals between degraded myofibrillar proteins, which could subsequently induce greater muscle fibre fragmentation and/or structural weakening during thawing resulting in an increase in meat tenderness (Mateo-Oyague & Perez-Chabela, 2004).…”
Section: Shear Force and Desmin Degradationmentioning
confidence: 98%
See 1 more Smart Citation
“…The loss of proteins, mostly sarcoplasmic protein, in the drip of previously-frozen bovine muscle has been reported by Howard et al (1960). The protein content of drip, calculated as percentage of total muscle protein, increased from about 5.86 for unfrozen muscle to 17.03 for muscle frozen for S weeks ( Table 2).…”
Section: Volume and Iprotein Content Of Dripmentioning
confidence: 90%